Participatory monitoring and evaluation in rural development: Capitalizing on the CHARM2 experience - Capegsan, Cecil B. (Technical Centre for Agricultural and Rural Cooperation, 2018)
A participatory monitoring and evaluation process was successfully applied as part of the Second Cordillera Highland Agricultural Resource Management Project, CHARM2. This is a special project implemented by the Philippines Department of Agriculture and is the second phase of the 1998-2004 CHARM1 project. This case study explores the work of the Barangay Participatory Monitoring and Evaluation Teams (BPMETs) in the 35 administrative divisions or barangays covered by CHARM2 in the province of Benguet. It shows how the information generated by the BPMETs has had an impact on policy making processes, and how the support provided for community empowerment initiatives continues to have a positive effect.